The Diagnosis and Treatment of Caesarean Scar Defect: Progress and Controversies - Zhuna Wu; Shunlan Liu; Fang Huang; Yumin Ke (IMR Press, 2023)
Objective: A caesarean scar defect (CSD), a niche in the uterus, is an emerging long-term complication after caesarean section (CS). With rising rates of CS, the risk of post-caesarean iatrogenic complications has increased, although many women may be diagnosed incidentally while asymptomatic. We present a review of the diagnosis and treatment of CSD. Mechanism: We describe the current state of treatment of CSD in terms of diagnosis and the different treatment options. Findings in Brief: The diagnosis can be confirmed by transvaginal sonography, hysteroscopy and other imaging examinations. At present, therapy is dependent on the presence of symptoms, the size of the CSD, and secondary infertility. Non-invasive management includes oral contraceptives and the levonorgestrel-releasing intrauterine system (LNG-IUS), which can improve the clinical symptoms of prolonged menstrual periods to some certain extent. Currently, the principal therapy is surgery, and micro-invasive surgical management includes transvaginal, hysteroscopic and laparoscopic procedures. However, there is no unified surgical selection standard, and the selection of surgical methods and the effect of surgical management are also controversial and need to be further studied. Conclusions: The aim of this review is to summarize and compare the selection of diagnostic and therapeutic methods and the differences in the curative effects of these therapeutic methods for CSD.